A longitudinal analysis of Corporate Social Responsibility Reporting (CSRR) in Malaysia public listed firms: pre- and post-mandatory csrr requirement - Zainal, D.; Zulkifli, N.; Saleh, Z. (2011)
The importance of corporate social responsibility reporting (CSRR) has been evident in Malaysia, particularly after the Bursa Malaysia mandated its reporting in firms’ annual reports from year 2007 onwards. Therefore, this study aims at examining the CSRR disclosed in the annual reports of Malaysia public listed firms over a five-year period, reflecting both voluntary and mandatory CSRR period. Sample of the study is drawn from firms that are listed in the main board of Bursa Malaysia and maintained their positions in top 300 firms over the five-year period. Results from the content analysis done reported an increase in both quantity and quality of CSRR by firms over the five-year period. The highest change in CSRR is found to be in year 2007, reflecting the first year when CSRR was made mandatory. More rigorous analysis is warranted to further investigate the effect of CSRR regulation on CSRR disclosed by firms.